Effects of Perceived Learning on Student Engagement among Undergraduate Students - *Dr. Iram Muzzamil; Dr. Zunaira Muzzamil; Dr. Zufishan Muzzami; Zuraiz Muzzamil (Review Journal of Social Psychology & Social Works, 2025)
This study investigated how student involvement was affected by perceived learning. Data was gathered from 200 B.Ed. students at two universities, one private and one public, using questionnaires regarding their perceptions of their education and participation in different study activities. Regression analysis was used in the study to reveal the detailed relationships between these variables, which gave educators and organizations seeking to improve learning outcomes important new information. The findings offer useful strategies to boost student participation and create a vibrant community of research in learning environments. The findings indicate that perceived learning is a key predictor of student involvement, and the model is statistically significant, it is highly improbable that the observed relationship is the product of chance. As a result, this enhanced perception fosters greater engagement. Engaged students are not only more likely to attend classes regularly and participate, but they are also more likely to take initiative, think critically, and persist through challenges. Over time, this level of involvement contributes to better academic outcomes, such as higher grades, improved retention, and stronger performance on assessments. Moreover, it increases intrinsic motivation, meaning students begin to learn not just for external rewards like grades, but because they genuinely value and enjoy the learning process.